ANALISIS TRANSAKSI JUAL BELI MELALUI E-COMMERCE DALAM PERSPEKTIF EKONOMI ISLAM - Uswatun Hasanah; Andi Cahyono (Program Studi Ekonomi Syariah, 2021)
The spread of the Corona Virus (COVID-19) which has hit Indonesia starting in 2020, has greatly impacted the lives of Indonesian citizens in various sectors of life. The visible impact is not only on public health, but also on the country's economy. The business sectors experienced a significant decline, inversely what happened in the business sector in e-commerce which experienced an increase during the COVID-19 pandemic. However, switching buying and selling transactions from offline to online through e-commerce poses its own questions for the public. Especially people who are not used to buying and selling transactions in e-commerce. How arebuying and selling transactions e-commerce in Indonesia? How is the law of buying and selling through e-commerce in the perspective of Islamic economics? As this study used methods of library research (libraryresearch) is research, carried out by collecting data and theoretical foundation of the search and penela'ahan various litetratur, then analyzed qualitatively and presented descriptively, that is explained, outlining in order to determine the form of the sale and purchase of e-commerce perspective ekonomi Islamic. The results obtained are buying and selling transactions through e-commerce are basically permissible (permissible) by fulfilling the rules that do not conflict with Sharia principles because transactions in e-commerce are the application of thecontract, salam or istishna' namely goods that are traded equally. deferred payments are made in advance and no one is harmed between the seller and the buyer, sobuying and selling e-commerce is halal in Islam. In addition,buying and selling transactions e-commerce also contain benefits in the form of convenience and time efficiency and are very suitable in the current pandemic mass, namely avoiding crowds (markets).